Pengaruh Nilai Pelanggan, Citra Merek (Brand Image) dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Kereta Api Kelas Ekonomi Tawang Jaya Jurusan Semarang-Jakarta (Studi Kasus di Stasiun Poncol DAOP IV, Semarang) - Yusuf Atstsaqifi; Handoyo Djoko Waluyo; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2015)
The goal of this study is to determine how customer value, brand image, and service quality affect the customers satisfaction of economic class of the Tawang Jaya Train which serves the Semarang-Jakarta route. Sampling technique used in this study is purposive sampling technique with samples gathered from 100 people. Linear regression analysis and significance test were used to test the hypotheses using SPSS 22.0. Result of data analysis concluded that partially the variables affected the customer satisfaction in a significant manner. Customer value to customer satisfaction in which t-count (6,880) > t-table (1,9845). Brand image to customer satisfaction in which t-count (9,845) > t-table (1,9845). Service quality to customer satisfaction in which t-count (9,744) > t-table (1,9845). Simultanously, all variable significantly affected customer satisfaction with F-count (42,459) > F-table (3,9391). As a suggestion to improve the customer satisfaction, PT KAI (Persero) DAOP IV Semarang and particularly Tawang Jaya Train should increase the cleanliness standard, improve the punctuality of train departure and arrival, balancing the price of food, drinks, and pillows in trains so it could become more affordable, resetting the seat location, and renewal of services SOP for the passengers.